Marisa Brown: capstone - Brown, Marisa, artist (Colorado State University. Libraries, 2015)
The artist's statement: My work emerges from my ongoing exploration of the natural world. The images unfold from a ritualistic relationship I have developed with nature. I seek to expose the interconnectedness between our world and our beings as well as reveal something about my own experiences. It's about reacting and responding to the world around me in order to reciprocate the energy it summons within me. I often leave my creations as temporal offerings to the forces of nature. My practice crosses into the realms of earth art, performance art, and installation but is deeply rooted in photography. Composing the image within the frame is when the work comes to life for the first time.
The sting between natural things
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.